2019
DOI: 10.1097/txd.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

Renal Outcomes of Liver Transplantation Recipients Receiving Standard Immunosuppression and Early Renal Sparing Immunosuppression: A Retrospective Single Center Study

Abstract: Background.New-onset stage 4–5 chronic kidney disease (CKD) after liver transplantation (LT) is associated with high morbidity, mortality, and economic burden. In 2010, we instituted an early renal sparing immunosuppression (RSI) protocol for LT recipients with severe renal dysfunction (pre-LT dialysis/estimated glomerular filtration rate (eGFR)<30mL/min/1.73 m2 or post-LT acute kidney injury) consisting of 2 doses of basiliximab for induction and delaying tacrolimus to post-LT day 4–7. We examined the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…( 27 ) We, similar to others, had previously reported the sex‐based differences in the relative risk of incident stage 4‐5 CKD after LT alone. ( 28,29 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 27 ) We, similar to others, had previously reported the sex‐based differences in the relative risk of incident stage 4‐5 CKD after LT alone. ( 28,29 )…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a higher risk of stage 4‐5 CKD and lower eGFR among NASH SLKT recipients compared with all other etiologies of liver diseases. NASH is also a risk factor for stage 4‐5 CKD after LT. ( 28 ) Because NASH is the leading indication for LT in females, ( 30 ) we examined the impact of this relationship on eGFR. This interaction was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Higher MELD and SAPS3 could impact in more severe AKI diagnosis, as previous described 33 , also higher liver ischemic times 14,32,34 and more vasopressor requirement 35,36 preclude AKI progression after liver transplantation. Brie y, sicker patients with higher vasoactive requirement and worse liver draft quality is going to experience more period and higher grade of post reperfusion syndrome 37 , denoting higher risk for AKI development and progression 14,38 .…”
Section: Discussionmentioning
confidence: 60%
“…Adopting tacrolimus as standard post-transplant immunosuppression agent is also a previous known strategy to amend kidney injury. In addition, better tacrolimus monitoring policies could also attenuate kidney injury occurrence 32 . However, in our analysis, the rst week peak tacrolimus trough concentration was not found to be signi cantly associated with development of AKI, possibly because recipients who are suspected to occurrence AKI receive a low dose and/or late introduction of calcineurin inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…70 Biomarkers of injury should be further explored; for example, urinary NGAL, when measured at 24 hours post-reperfusion has been shown to be independently associated with CKD at 5 years post-liver transplant. 71 Kidney injury-sparing immunosuppressive strategies should be further developed and may include delayed calcineurin inhibitor introduction to promote renal recovery for those with post-operative renal dysfunction, 72,73 and later CNI conversion with novel immunosuppressive agents such as belatacept. Ideally, future studies may test interventions based upon these preliminary findings…”
Section: Ckd: Current Status and Future Directionsmentioning
confidence: 99%